DESIGN OF A HOMEMADE BIOFILTER FOR DOMESTIC WASTEWATER TREATMENT IN THE SITU RAWA BESAR - Syarifah; Taqi Muhammad Javani; Latricia Aina Hidayat; Kesatria Sughani; Jerry Maratis; Andri Krisna Hidayat; Ahmad Irfandi (Universitas Medan Area, 2026)
Water pollution from domestic wastewater is one of the main causes of eutrophication in public waters, including the Rawa Besar Lake in Depok. Eutrophication is characterized by an explosion of algae growth that leads to a decrease in dissolved oxygen and the death of aquatic life. This research aims to design a simple (homemade) biofilter technology using local media such as red brick, zeolite, and ceramic rings that is accessible and easily accessible to the public to purify household wastewater before it is discharged into the environment. The research method uses an experimental Research and Development (R&D) approach, involving the design, fabrication, and performance testing of a small-scale biofilter prototype. Wastewater quality was evaluated before and after treatment by measuring turbidity, odor, and pH as key indicators of treatment effectiveness. The results showed that the biofilter reduced water turbidity, eliminated unpleasant odors, and stabilized wastewater pH toward neutral conditions, indicating effective removal of suspended solids and organic contaminants. The results of this study indicate that the biofilter technology developed effectively treats contaminated water by changing the turbidity, odor and pH of the wastewater. This biofilter is designed for easy domestic use, at a low cost, and with an ecological approach.